Social Marketing Strategy Through Digital Campaigns as an Effort to Reduce Plastic Waste in Kupang City - Maria Sisilia Lou Kelen; Taqwa Sultan; Margaretha Sartien Kabanga (Economics and Digital Business Review, 2026)
Through changing public perception in reducing the use of single-use plastics through the digital campaign "Plastic Efficiency." The campaign aims to increase awareness and encourage changes in people's behavior in the use and management of plastics more responsibly. This research focuses on designing digital campaigns using the 5A Kotler model consisting of Aware, Appeal, Ask, Act, and Advocate. This approach is a modern marketing strategy that is relevant to the connectivity era because it is able to build audience engagement while increasing public awareness of plastic issues. This campaign is also expected to support the government's "Kupang Green and Clean 2025" program. The 5A Kotler model is used by incorporating messages that have emotional appeal to build audience response and engagement. The research uses qualitative methods through in-depth interviews, questionnaires, and Focus Group Discussions (FGDs). The campaign content is then integrated through social media and evaluated using engagement metrics and surveys to identify changes in people's behavior.